A Case Report : Recurrent Herpes Labialis In A 12 Year Old Boy - Putu Mahadevy Pradnyandhari Putri; Ida Ayu Uttari Priyadarshini; Putu Ayu Paramitha Saraswaty (The International Journal of Medical Science and Health Research, 2024)
Introduction: Herpes labialis, commonly known as cold sores, is an infection predominantly caused by herpes simplex type 1 (HSV-1).  Transmission of herpes labialis occurs through direct contact with active lesions or bodily fluids, including saliva, from infected individuals. Patients with herpes labialis often report prodromal symptoms before lesions appear, such as fever, fatigue, loss of appetite, and muscle aches. Localized symptoms, including pain, burning, or itching at the site of the impending eruption, are also common. This case report discusses a recurrent herpes labialis case at Wangaya Regional General Hospital, aiming to enhance understanding of the condition's presentation, management strategies to prevent recurrence, and measures to minimize transmission. Case Report : A 12-year-old boy was diagnosed with recurrent herpes labialis caused by an infection with herpes simplex virus type 1 (HSV-1). This diagnosis was based on the patient's medical history, which indicated prodromal symptoms and polymorphic lesions, as well as dermatological examination findings that showed herpetiform vesicles with crusting. The patient’s history of similar symptoms and the lesion’s localization to the vermillion border of the lips support the diagnosis of a recurrent infection. Herpes labialis is most commonly seen in children, particularly those under 19 years of age, which corresponds with the patient’s age. The primary risk factor is direct contact with an infected individual, which aligns with the patient's history of frequently sharing food and drinks with a friend who also exhibited similar symptoms. Additionally, the patient was known to share electronic cigarettes (vapes) with schoolmates. Recurrent herpes labialis can be triggered by various factors, including weakened immunity and UV exposure, both of which were present in this case.   Conclusion: The main treatment provided for this patient was oral acyclovir. The use of acyclovir aims to reduce symptoms, accelerate healing, and lower the risk of infection transmission. Acyclovir works by inhibiting viral replication through the suppression of DNA polymerase, which reduces the amount of active virus and speeds up recovery. The dosage of acyclovir given to the patient was in accordance with recommended guidelines. Supportive diagnostic tests, such as serology or Tzanck smear, are recommended to confirm the diagnosis. However, in this case, the diagnosis was already established through medical history and physical examination. Given that this is a contagious disease, the patient was educated on measures to reduce the risk of transmission.